The Present Educative Reforms in Latin America: Four Actors, Three logics and Eight Tensions - Cecilia Braslavsky; Gustavo Cosse (Universidad Autónoma de Madrid, 2018)
This document tries to recover some reflections produced by the "symbolic analysts" about certain aspects of the dynamics established to take care of the educational challenges of the present reforms in Latin America. In the first part of the document the educational reforms is characterized. Then, a common aspect in these reform is specified : the pretension to reform the State. In the third section some elements of the educational reforms appear, organized like "tensions", from the perspective of the "intellectual reformers". Finally, some conclusions appear respect to the cultures in struggle behind the tensions that are pronounced in the processes of management of the educational reforms. Original reference: Braslavsky, C. y Cosse, G. (1996). Las actuales Reformas Educativas en América Latina: Cuatro Actores, Tres Lógicas y Ocho Tensiones. Santiago de Chile: PREAL.